Unlocking the Potential of Continue Intention to Use of MyBCA between Generations - Aji, Fajar; Akbar, Mohammad Ali; Adhitya, Ervin; Rahim, Rano Kartono (Journal of Business & Banking, 2023)
BCA has just unveiled a brand-new digital platform called myBCA. Although myBCA provides more services overall than mobile BCA, users are hesitant to transfer over due to concerns about security. The myBCA app's rating in the Google Play Store is still 3.7 stars. This situation is emblematic of common challenges encountered in the digital landscape, where the introduction of new technologies often meets with user resistance, especially when security and usability concerns arise. The acceptance and continuance of using new technology are explained by TCT. There are three primary factors—e-service quality, perceived ease of use, and perceived risk—that affect how new technology is accepted. This research uses primary data involving 250 respondents. The data were analysed using structural equation models. The results showed that e-service quality and perceived ease of use have a significant and positive effect on user satisfaction. Yet, e-service quality directly has no significant effect on continued intention to use. Perceived risk has a negative impact on user satisfaction, both directly and indirectly, on continued intention to use. User satisfaction is able to mediate the influence of e-service quality, perceived ease of use, and perceived risk on continued intention to use the MyBCA app. Perceived ease of use is more sensitive to Gen Y and Gen Z, while perceived risk is more sensitive to Gen Y. The implication of this study suggest that companies should prioritize e-service quality and perceived ease of use while developing new technology.